Students’ perspectives on the mentorship program implemented for first year MBBS students: a cross sectional study - Xaviour, Rosemol; V., Sruthi M. (International Journal Of Community Medicine And Public Health, 2022)
Background: Medical profession is a transition stage from school life to college life where the students were subjected to vast changes in the syllabus, teaching and learning methods and a new environment with a new set of teachers and friends. As a result, many feel stressed and quite a few had dropped the course. To help the budding medicos Kerala University of Health Sciences has started a Student Support and Guidance Programme under which we the first-year faculty arrange mentoring sessions for the first year MBBS students. The present study was intended to know the effectiveness of mentorship programme implemented for first-year MBBS students. Methods: A cross-sectional study was carried out, among first-year undergraduate medical students of our medical college from January 2019 to June 2019. 110 students out of total 150 returned the filled questionnaire and this data was coded and entered in micro soft excel and analysed using SPSS version 2 software. Results: Overall rating of the mentorship program signalled it as heart-warming for the students. Around 64% of students had an opinion that a mentoring programme is needed for all students. Conclusions: In-depth sessions and more interactions with students might help the institution to harness responsible confident future doctors as they feel they are an asset to the institution and society.